Pheochromocytoma, Paraganglioma and Neuroblastoma - Cianci, Pasquale; Restini, Enrico; Agrawal, Amit (IntechOpen, 2021)
Pheochromocytoma, paraganglioma and neuroblastoma are the most common neural crest-derived tumors in adults and children, respectively. These neoplasms are associated with significant morbidity and mortality. Some international studies currently underway are researching and evaluating the presence of any similarities and differences between these tumors. Hopefully, future results will reveal several potential novel genes and pathways that might have major roles in the pathogenesis and progression of these neoplasms. This book discusses epidemiology, genetics, and treatment of these malignancies.